Pelatihan Model Kepemimpinan Transformasional dalam Menumbuhkan Rasa Percaya Diri Siswa - Grecetinovitria Merliana Butar-butar; Chintya Megaria Situmeang; Ronal Sagala; Haposan Silalahi (Pusat Riset dan Inovasi Nasional, 2023)
Leadership Basic Training is an activity that is commonly carried out in the school environment in an effort to train students to become leaders in the future. The Basic Leadership Training aims to cultivate and maximize the leadership potential that exists in students. Based on field observations, the Basic Leadership Training has never been carried out at SMK Cahaya Negeri Sidikalang. This Community Service Activity is carried out in the form of Transformative Leadership Training activities in Growing Confidence in Students of SMK Cahaya Negeri Sidikalang. The results of the service showed an increase in the score from the pre-test with an average pre-test score of 4.23, an increase with an average post-test score of 7.83. The increase in students' abilities after the pre-test and post-test was carried out with an average of 3.6 points. This indicates that transformational leadership training has benefits and positive impacts.